Finite Element Analysis of PMMA Stretch Blow Molding. (27th August 2014) - Bougharriou, Afef; Jeridi, Mohieddine; Hdiji, Mohamed; Boughrira, Anoir; Saï, Kacem
Abstract : The electric bubbles are a useful product made of PMMA material. They are produced by the stretch blow molding process. Thickness, which reflects the quality of the electric bubble, is a crucial parameter that deserves special attention for the molding process. In this work, finite element simulations of the stretch blow molding process are performed aiming at the determination of the preform geometry to ensure homogeneous thickness of the finished product. The geometrical parameters of the preform are optimized allowing a better homogeneity thickness compared to existing data. The predicted parameters allow the improvement of the thickness distribution. The standard deviation of the thickness is reduced to about 95% compared to the existing bubble.